Enzyme assisted extraction of pectin and inulin enriched fractions isolated from microwave treated Cynara cardunculus tissues. (10th August 2020) - Santo Domingo, Cinthia; Otálora González, Carlos; Navarro, Diego; Stortz, Carlos; Rojas, Ana M.; Gerschenson, Lía N.; Fissore, Eliana N.
Summary: Artichoke flower heads are consumed fresh or industrialized. Agroindustrial by‐products of this plant can be used for the production of dietary fiber. A microwave heating procedure is proposed for polysaccharides concentration in the residues. It consumed less time (36 min vs 75 min) and solvent volume (110 mL vs 140 mL) and allowed the extraction of a higher amount of total carbohydrates (95 g/100g vs 83 g/100g) than the habitually used convective procedure. A subsequent stage involving buffer/enzymes allowed to isolate pectin and inulin enriched fractions. Their inulin content was 32–45 g/100g. The galacturonic acid content oscillated between 22 and 29 g/100g. The fractions were slightly yellow/red colored and formed gels in the presence of calcium ion. The procedure proposed is of importance in the frame of emerging biorefinery because it uses vegetable by‐products to produce fractions with potential for being used in the formulation of healthy foods. Abstract : The extraction of pectin and inulin enriched fractions from the microwave‐treated alcohol insoluble residue (AIR) of artichoke bracts and stems.